The Role of Women Entrepreneurship and Eco-Friendly Entrepreneurship on Market Orientation and Marketing Performance of Female Entrepreneurs - Windiyani Windiyani; Rahmad Solling Hamid; Sofyan Syamsuddin; Muhammad Ikbal (Proceedings Series on Social Sciences & Humanities, 2024)
Background: In contemporary business landscapes, women entrepreneurs have emerged as a significant driving force, contributing to economic growth and innovation. Simultaneously, eco-friendly entrepreneurship has gained prominence, reflecting a growing global awareness of environmental sustainability in business practices. This study aims to examine the synergy between women's entrepreneurship and eco-friendly initiatives in shaping market orientation and marketing performance among female entrepreneurs. Method: The empirical analysis was conducted using a sample of 131 female entrepreneurs. This study used online survey for the data collection. After passing reliability and validity tests, the data were analyzed with partial least squares structural equation modeling. Results: The research results indicate that women entrepreneurship has a significant positive direct influence on market orientation. Eco-friendly also has a significant direct positive influence on market orientation. Finally, market orientation also has a significant positive influence on market performance. Conclusion: This study illuminates the intertwined dynamics of women's entrepreneurship and eco-friendly practices in influencing market orientation and marketing performance among female entrepreneurs. The findings underscore the potential for sustainable, gender-inclusive business strategies to not only drive business success but also contribute to environmental stewardship and societal progress. As women continue to play a pivotal role in the entrepreneurial landscape, fostering eco-friendly entrepreneurship offers a promising avenue for holistic economic and environmental advancement.